Dampak Penerimaan Peserta Didik Baru (PPDB) Sistem Zonasi (Studi Kasus: Penerimaan Peserta Didik Baru Sekolah Dasar di Kecamatan Matur) - Fanni Putri Salim; Desri Nora (Naradidik: Journal of Education and Pedagogy, 2022)
This study aims to determine the New Student Admission (PPDB) zoning system in the Matur District Elementary School (SD). This research was motivated by Permendikbud No. 1 of 2021 regarding the acceptance of new students. One of the regulations that must implemented in this permendikbud is the student addmissions path which is divided into 4 pathways including the zoning path, the affirmation path, the transfer path of parental duties and the achievement path. This study was analyzed using the Structural Functional Theory of Robert K. Merton, using a qualitative approach with the type of case study research. The selection of informans was carried out using purposive sampling technique with a total of 30 informants. Data was collected by means of observation, interviews and documentation studies. The result of the study found that the new students admissions (PPDB) with a zoning system in Matur District had a positive impact including minimizing the perspective of superior schools, equalizing education, facilitating parental supervision. The negative impact is the acquisition of new students in religious eduction institutions, the potential for cheating parents and closing or regrouping schools.